2018
DOI: 10.9734/ejmp/2018/41587
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic and Biochemical Effects of the Aqueous and Methanolic Extract of Persea americana Seeds on Alloxan-Induced Albino Rats

Abstract: The increase in the prevalence, complications and cost effect of diabetes management necessitated the search for alternative treatment and a look into the anti-diabetic and biochemical effects of Persea americana seed extract on the liver of diabetic rats. This study was conceived and designed based on the gaps in the research that has been performed and what is known about the plant. The anti-diabetic and biochemical effects of both the water and ethanol extracts of Persea americana (avocado pear) seed on all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 25 publications
5
26
0
5
Order By: Relevance
“…The biochemical analyses carried out however revealed a significant increase (p < 0.01) in the amount of either AST or ALT, respectively for group AE and ME as compared to the control group. In this study, the ratio AST/ALT, which fell respectively at 2.35 and 1.29 for groups EE and ME, indicates an abnormality as to the hepatic function of the liver; thus, confirming the outcomes of the study performed (Ezejiofor et al, 2013). On the other side, these results displayed the leaves of P. americana to be of lesser toxicity than that of the ripe fruit's seeds extracts.…”
Section: Persea Americanasupporting
confidence: 86%
See 1 more Smart Citation
“…The biochemical analyses carried out however revealed a significant increase (p < 0.01) in the amount of either AST or ALT, respectively for group AE and ME as compared to the control group. In this study, the ratio AST/ALT, which fell respectively at 2.35 and 1.29 for groups EE and ME, indicates an abnormality as to the hepatic function of the liver; thus, confirming the outcomes of the study performed (Ezejiofor et al, 2013). On the other side, these results displayed the leaves of P. americana to be of lesser toxicity than that of the ripe fruit's seeds extracts.…”
Section: Persea Americanasupporting
confidence: 86%
“…Especially, flavonoids exhibited a protecting effect against toxicity and oxydating stress. On the other hand, saponines also demonstrated an antihyperglyceamic effect due to inhibition of glycogenesis (Elekofehinti, 2015;Ezejiofor et al, 2013).…”
Section: Persea Americanamentioning
confidence: 99%
“…The hypoglycemic and tissue‐protective effects of the hot‐water extract of P. americana seeds (20, 30, 40 g/L, for 3 weeks) were investigated in AID rats. It was shown that the extract had a significant hypoglycaemic effect and reversed the histopathological damage that occurred in AID rats, comparable with the effects of glibenclamide (Ezejiofor et al , ). Reduction in oxidative stress, lipid peroxidation, and reactive oxygen species production was observed in the liver mitochondria of the SID rats which were treated with avocado oil (4 mL/kg) for 3 months.…”
Section: Introductionmentioning
confidence: 70%
“…It is also known as ‘alligator pear’ or ‘butter pear’ (Lacerda et al , ). Avocado is consumed, not only for its flavor, but also for its high nutritional value and beneficial health effects (Meyer and Terry, ) including hypoglycaemic (Ezejiofor et al , ), antihypertensive (Dzeufiet et al , ), antioxidant (Nagaraj et al , ), anti‐obesity (Monika and Geetha, ), hypolipidemic (Pahua‐Ramos et al , ) (Fig. ), antilithiasis (Wientarsih et al , ), anticonvulsant (Ojewole and Amabeoku, ), antimicrobial (Pradeep et al , ), antiprotozoal and antimycobacterial (Jiménez‐Arellanes et al , ), hepatoprotective (Mahmoed and Rezq, ), antiosteoarthritis (Christiansen et al , ) and chemo‐protective (Paul et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, el área bajo la curva del aumento de intolerancia a la glucosa fue menor en el grupo con la dieta estándar + sacarosa + 5% aceite de palta, con respecto al grupo con la dieta estándar + sacarosa 31 . El extracto acuoso de semilla de palta también tendría actividad hipoglicémica y protectora tisular en páncreas, hígado y riñones en ratas Wistar albinas 10 . Sumado a esto, Tabla 1.…”
Section: Efecto Cardiometabólicounclassified